The impact of non-steroidal anti-inflammatory drugs use in elderly cardiovascular patients: an observational study from tertiary care in South India - Sharma, Sadhna; Govind, Biju; Rao, Kondal (International Journal of Research in Medical Sciences, 2019)
Background: Long-term use of NSAIDs, by patients having cardiovascular conditions, has shown to increase the risk of cardiovascular events and increased risk of death. Hence, the study was conducted to determine the complications related to NSAID use by the elderly patients with cardiovascular disease (CVD). Methods: The study was a single-center prospective observational study conducted November 2017 to October 2018. Elderly patients (>60 years) suffering from various CVDs and reported NSAID intake daily for at least one month were included. A questionnaire included demographic, treatment related history and complete details of NSAIDs intake including nature, dose, indication, source etc. The same questionnaire was again filled at the end of one-year follow-up. Results: A total of 100 participants were included in the study. The mean age was 72±8.6 years. Majority of the patients (93%) had hypertension, and 69% of the patient had previous MI. Five NSAIDs (diclofenac, ibuprofen, mefenamic acid, naproxen, and ketorolac) were used routinely. At least one over the counter NSAID used was reported by 86%, 57% were prescribed at least one NSAIDs by their orthopaedics and physicians. At the end of 1-year follow-up, authors found that 71% had MI (2% increase), 4% developed reinfarction, 20% had severe left ventricular failure (4% increase), 7% had atrial fibrillation (1% increase), and 2% patients died and 63% patients reported raise in systolic blood pressure by 5mmHg. Conclusions: High prevalence of concomitant NSAID use among elderly CVD patients, which might be contributing towards increase in CVS morbidity and mortality.